Madrasah Head's Strategy in Overcoming the Limitations of Learning Facilities and Infrastructure - Rifana Rifana; Syahril Syahril; Mastura Minabari (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the strategy of madrasah heads to overcome the lack of learning facilities and infrastructure at MTs Alkhairaat Tomini. Limited access to educational facilities is a significant obstacle in improving the quality of education and the effectiveness of the teaching and learning process in madrasas. This research aims to find out the strategies used by madrasah heads in managing and overcoming the needs of learning facilities and infrastructure. This research uses a qualitative methodology with a descriptive framework. Data collection methods include observations, interviews, and recordings involving informants such as madrasah heads, teachers, and students. The findings of the study show that madrasah heads implement various strategies, including optimizing the use of facilities, encouraging collaboration with committees and the community, seeking government assistance, and encouraging teachers' creativity in utilizing basic learning media. This solution effectively supports the sustainability of the learning process despite limited facilities and infrastructure. This research advances education management, especially in the leadership of madrasah heads in the management of educational facilities.  The results of this study are an important reference for other madrassas that face similar challenges